2012
DOI: 10.2217/ahe.12.43
|View full text |Cite
|
Sign up to set email alerts
|

Social Determinants and Osteoarthritis Outcomes

Abstract: Osteoarthritis (OA) is one of the most frequently occurring musculoskeletal diseases, posing a significant public health problem due to its impact on pain and disability. Traditional risk factors fail to account for all of the risk observed for OA outcomes. In recent years, our view of disease causation has broadened to include health risks that are created by an individual’s socioeconomic circumstances. Early research into social determinants has focused on social position and explored factors related to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
90
0
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(103 citation statements)
references
References 153 publications
(167 reference statements)
3
90
0
3
Order By: Relevance
“…State anxiety studies indicate that it results from the individual's dispositions and situational variables; thus there is no clarity as to the adaptability of coping style values (Luong et al, 2012;Endler, 1997;Smith & Wallston, 1996). It seems that the results presented by the authors confirm certain positive aspects of task-oriented coping and the orientation to give positive meaning to difficulties.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…State anxiety studies indicate that it results from the individual's dispositions and situational variables; thus there is no clarity as to the adaptability of coping style values (Luong et al, 2012;Endler, 1997;Smith & Wallston, 1996). It seems that the results presented by the authors confirm certain positive aspects of task-oriented coping and the orientation to give positive meaning to difficulties.…”
Section: Discussionmentioning
confidence: 85%
“…However, Carver and others (1989) claim that the idea of "stable coping dispositions" is "somewhat controversial" (p.270). Apart from coping, the researchers pay attention to perceived social support as a factor supporting mental balance in OA (Luong et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…As would be expected, both income and education had a protective effect on disability in this study. SES characteristics like income and education, however, do not directly affect disability, but operate through other factors such as lifestyle choices (smoking, alcohol consumption, diet, or physical exercise) or psychological factors (perceived helplessness, social support and perceived discrimination) (Everson et al 2002;Hagen et al 2006;Luong et al 2012;Newbold and Neligan 2012). For example, studies have shown that obesity and low physical exercise are associated disability (Baumgartner et al 2004;Peters et al 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Social inequity plays an important role in the prevalence of chronic diseases [1,2], but information related to rheumatic diseases is still scarce [3,4]. Few studies have identified the existence of inequities among patients with rheumatoid arthritis (RA) [4], osteoarthritis (OA) [5], and systemic lupus erythematosus [6] in any country.…”
Section: Introductionmentioning
confidence: 99%